Humble Exclusivism: Solusi Wacana Etis Otoritas Keagamaan di Ruang Digital - Muhamad Aulia Kemal Fasas (Journal of Religion and Social Transformation, 2025)
The digitalization of religious authority faces a moral and epistemic crisis driven by social media's algorithmic logic, which favors performative popularity over institutional knowledge. This research aims to formulate "Humble Exclusivism" as an Islamic ethical framework to address this tension. The study employs a qualitative-descriptive method with a library research approach, integrated within the Digital Islamic Studies framework. The findings demonstrate that humble exclusivism functions as an ethical paradigm emphasizing epistemic humility and moral accountability, thereby shifting legitimacy from algorithmic visibility back to the moral domain. The study concludes that this framework provides a viable model for contemporary authority, implying the need for digital da’wah to prioritize ethical responsibility over engagement metrics.